2000
DOI: 10.1034/j.1600-0765.2000.035005291.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytostatic action of enamel matrix derivative (EMDOGAIN®) on human oral squamous cell carcinoma‐derived SCC25 epithelial cells

Abstract: During surgical treatment of periodontal disease, enamel matrix derivative (EMD) is topically applied as a substitute for extracellular matrix in order to facilitate regeneration of damaged periodontal tissue. However, the mechanism for EMD action is poorly understood. We have now examined the effects of EMD on the proliferation of oral epithelial (SCC25) cells in vitro. After 3 days of treatments, EMD (25 100 microg/ml) dose-dependently inhibited cell division and concomitantly arrested cell cycle at the G1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
97
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 15 publications
16
97
1
3
Order By: Relevance
“…EMD enhances the adhesion, proliferation and matrix production of fibroblast-like but not epithelial cells (Cattaneo et al, 2003;Gestrelius et al, 1997;Haase and Bartold, 2001;Hoang et al, 2000;Kawase et al, 2000). Attachment of human periodontal ligament cells to EMD is possibly mediated by bone sialoprotein as it can be inhibited by RGD-containing peptides or with an anti-avb3 integrin antibody (Suzuki et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…EMD enhances the adhesion, proliferation and matrix production of fibroblast-like but not epithelial cells (Cattaneo et al, 2003;Gestrelius et al, 1997;Haase and Bartold, 2001;Hoang et al, 2000;Kawase et al, 2000). Attachment of human periodontal ligament cells to EMD is possibly mediated by bone sialoprotein as it can be inhibited by RGD-containing peptides or with an anti-avb3 integrin antibody (Suzuki et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to identity the cytokines in EMD, with varying results. Kawase et al (65,80), and later Suzuki et al (48), identified TGF-β1, or TGF-β-like substances, in EMD, which they believed to be the main functional components. Furthermore, EMD enhances the production of TGF-β1 in many different cell lines, including osteoblasts, fibroblasts, and malignant osteosarcoma cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…No differences in the proliferation of fibrosarcoma HT-1080 cells or breast cancer-derived MCF-7 cells were observed after EMD treatment (55,79). EMD decreased proliferation of human cervix-derived epithelial HeLa cells, human osteosarcoma MG-63 cells, and human squamous cell carcinoma-derived SCC-25 cells (39,56,80). One study found that EMD dose-dependently arrested the SCC-25 cell cycle at G1 and did not discernibly increase SCC-25 apoptosis during eight days of treatment (80).…”
Section: Emdogain and Malignant Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…EMD has already been commercialized (known commercially as Emdogain ® Gel), and is currently the only substance that uses biologically active proteins for the regeneration of periodontal tissue to have been approved by the Japanese Ministry of Health, Labour and Welfare. However, despite much effort to elucidate the molecular mechanism of EMD action, no unified opinion has been reached regarding its effects on the regeneration of periodontal tissue [1], its inhibition of downgrowth of the gingival epithelium [2], or its anti-inflammatory action [3]. Additionally, since the product is a foreign protein derived from porcine tooth germ, some health issues such as the possibility of allergic reactions and contamination with unknown viruses cannot be completely excluded, although no harmful effects have been reported [4].…”
Section: Introductionmentioning
confidence: 99%